The role of imaging and other diagnostic approaches in COVID-19 - Shammus, Rohma; Mahbub, Samiha; Rauf , Muhammad Atif; Harky, Amer (Acta Biomedica Atenei Parmensis, 2020)
As the COVID 19 pandemic develops across the globe, a large amount of literature has been written about the different ways in which we can diagnose and investigate someone suspected of being infected with the new coronavirus. Many approaches highlight the importance of using reverse transcriptase polymerase chain reaction (RT-PCR) used in conjunction with computed tomography (CT) scans. Whilst CT scans have been shown to be useful, there are multiple risks associated with them, for example radiation exposure and the transmission risk associated with repeated use of a CT suite. Therefore, it is important to analyse their diagnostic ability and limitations and to consider other methods of diagnosing COVID 19. Additionally, RT-PCR testing can have significant rates of false negatives, indicating the importance of taking a more comprehensive diagnostic approach. Here, we aim to review and analyse this literature to compare RT-PCR, serum inflammatory biomarkers, chest radiographs, ultrasound and chest CT scanning as methods of diagnosing COVID 19, particularly in asymptomatic patients.